Professional Values and Practice - Arthur, James (Taylor & Francis, 2005)
The professional code of the General Teaching Council lists eight new standards, each of them analysed here in detail using questions and activities to describe what trainee teachers need to know, understand and demonstrate as they work towards Qualified Teacher Status. Each of the eight standards cover the following issues: expectations, diversity and achievement personal and professional values values in the classroom values, rights and responsibilities in the wider community the community of the school professional relationships personal and professional development professional responsibility. This practical and jargon-free guide features an extensive range of examples and suggestions for further reading, designed to help those in their early professional development.